Dinámica en el comercio exterior y factores de competitividad de los puertos de Cartagena, Barranquilla y Santa Marta entre los periodos 2015-2020 (2022)
The ports are a key piece for regional and national economic development, as well as for participation in international markets. Therefore, the different characteristics associated with port logistics, location and infrastructure become strategic factors that promote intra-regional and international commercial dynamics. In this sense, the present monograph had as a general objective Describe the dynamics of foreign trade and the factors of competitiveness of the Caribbean ports; Cartagena, Barranquilla and Santa Marta between the periods 2015-2020. Through a descriptive-analytical methodology, a deductive method based on a documentary review and comparative analysis of the characteristics, challenges, opportunities, and operational processes of ports, thus allowing understanding, and strengthening knowledge about the operation port in the Colombian Caribbean Region. From the results obtained, it is highlighted that the ports in question have an optimal installed capacity and have efficient logistics that favor maritime operations of cargo transport, to meet the demands of foreign trade at a national and international level.